Developmental Improvement and Age-Related Decline in Unfamiliar Face Matching. (January 2015) - Megreya, Ahmed M; Bindemann, Markus
Age-related changes have been documented widely in studies of face recognition and eyewitness identification. However, it is not clear whether these changes arise from general developmental differences in memory or occur specifically during the perceptual processing of faces. We report two experiments to track such perceptual changes using a 1-in-10 (experiment 1) and 1-in-1 (experiment 2) matching task for unfamiliar faces. Both experiments showed improvements in face matching during childhood and adult-like accuracy levels by adolescence. In addition, face-matching performance declined in adults of the age of 65 years. These findings indicate that developmental improvements and aging-related differences in face processing arise from changes in the perceptual encoding of faces. A clear face inversion effect was also present in all age groups. This indicates that those age-related changes in face matching reflect a quantitative effect, whereby typical face processes are engaged but do not operate at the best-possible level. These data suggest that part of the problem of eyewitness identification in children and elderly persons might reflect impairments in the perceptual processing of unfamiliar faces.